Directivity enhancement of 60 GHz microstrip patch antennas using dielectric fabry-perot resonantors - Arvas, Müberra (İstanbul Medipol Üniversitesi Fen Bilimleri Enstitüsü, 2019)
The 60 GHz frequency band offers many opportunities for innovations in the wireless network technology, unlike other bands. Since the wavelength in the 60 GHz band is millimetric, this band can suitably represent the line-of-sight LoS part of the wireless communication. It offers superior features in inter-building, near-point and point-to-point wireless networking applications. Nevertheless, and despite its superior properties, this band is prone to a highly effective attenuation in the terrestrial plane (sea level). The reason for this attenuation is that the gases in the atmosphere absorb the signals, especially the coercive behavior of the oxygen molecule around its resonance line in the 60 GHz frequency band. This phenomenon, called oxygen weakening, is the most important drawback that this band suffers. Ironically, this attenuation might be seen as an advantage because it allows reuse of the frequency channels. This thesis is concerned with the propagation of electromagnetic waves in the 60 GHz frequency band from two distinct aspects. First, an attempt to physically model the atmospheric absorption is made. This objective has been achieved by developing a new material model for the atmosphere based on Lorentz functions. The developed model is by far more superior, and more useful, than the existing empirical model. Whereas the applicability of the empirical equations are very limited to ray-tracing propagation methods, the physical model developed in this thesis enjoys unlimited applicability in propagation problems involving the atmosphere because it can be easily incorporated in most electromagnetic simulators. A home-grown time-domain simulation algorithm based on the time-domain finite-difference method (FDTD) has been built and quantitatively tested. In the second part of the thesis, the directivity enhancement of a basic patch antenna which operates at 60 GHz is addressed. Enhancing the directivity of the antenna is an effective design strategy in LoS communication links to overcome channel loss caused by the atmosphere. A design based on the Dielectric Fabry-Perot Resonator (DFPR) has been developed. Extensive parametric studies on the resonator operation and its effect on the antenna directivity have been performed using a commercial software. When the results are examined, it is shown that the best directivity of the DFPR-based patch antenna is obtained when the antenna resonance is matched to the DFPR resonance. Other design guidelines were also identi ed and explained. The work done in this thesis opens several directions for further research on different fronts including the atmospheric propagation model as well as directivity enhancement. Possible extensions can be in the range of applicability of the time-domain propagation model as well as the effect of dielectric resonators built around the patch antenna.

60 GHz frekans bandı, diğer bantlardan farklı olarak, kablosuz ağ teknolojisindeki yenilikler için birçok fırsat sunar. 60 GHz bandındaki dalga boyu milimetrik olduğundan, bu bant uygun şekilde kablosuz iletişimin görüş hattı LoS bölümünü temsil edebilir. Binalar arası, yakın-noktaya ve noktadan noktaya kablosuz ağ uygulamalarında üstün özellikler sunar. Bununla birlikte, ve üstün özelliklerine rağmen, bu bant karasal düzlemde (deniz seviyesi) oldukça etkili bir zayıflamaya eğilimlidir. Bu zayıflamanın nedeni, atmosferdeki gazların sinyalleri emmesidir, özellikle oksijen molekülünün 60 GHz frekans bandında rezonans hattı etrafındaki zorlayıcı davranışıdır. Oksijen zayıflaması denilen bu fenomen, bu bandın karşılaştığı en önemli dezavantajdır. Tezat olarak, bu zayıflama, frekans kanallarının tekrar kullanılmasına izin verdiği için bir avantaj olarak görülebilir. Bu tez 60 GHz frekans bandındaki elektromanyetik dalgaların iki farklı yönden yayılımı ile ilgilidir. İlk olarak atmosferik soğurmayı fiziksel olarak modelleme denemesi yapılmıştır. Bu amaca, Lorentz fonksiyonlarını temel alan atmosfer için yeni bir materyal modeli geliştirilerek ulaşılmıştır. Geliştirilen model, mevcut ampirik modelden çok daha üstündür, ve daha kullanışlıdır. Ampirik denklemlerin uygulanabilirliği ışın-izleme yayılım yöntemleriyle çok sınırlı olsa da, bu tezde geliştirilen fi ziksel model atmosferi içeren yayılma problemlerinde sınırsız uygulanabilirliğe sahiptir. Çünkü çoğu elektromanyetik simülatöre kolayca dahil edilebilir. Sonlu farklar zaman alanı yöntemine (FDTD) dayalı yerli bir zaman-bölge simülasyon algoritması oluşturulmuştur ve nicel olarak test edilmiştir. Tezin ikinci bölümünde, 60 GHz'de çalışan temel yama anteninin yönlülük arttırılması ele alınmıştır. Antenin yönlendiriciliğinin arttırılması, LOS iletişim bağlantılarında atmosferden kaynaklanan kanal kaybının üstesinden gelmek için etkili bir tasarım stratejisidir. Dielektrik Fabry-Perot yankılayıcısına dayanan bir tasarım geliştirilmiştir. Rezonatörün çalışması ve anten yönlülüğü üzerindeki etkisi üzerine kapsamlı parametrik çalışmalar ticari bir yazılım kullanılarak yapılmıştır. Sonuçlar tetkik edildiğinde, DFPR temelli yama antenin en iyi yönlülüğünün, anten rezonansı DFPR rezonansıyla eşleştiğinde elde edildiğini göstermektedir. Diğer tasarım kılavuzları da tanımlanmıştır ve açıklanmıştır. Bu tezde yapılan çalışmalar atmosferik yayılım modelleme ve yönlülüğün arttırımı dahil olmak üzere farklı cihetlerde daha ileri araştırmaların yapılması için bir çok kapı açmaktadır. Bu tez konusuna dair olası eklemeler, zaman-bölge yayılımı modelinin uygulanabilirlik aralığı ile yama anteninin etrafına yerleştirilmiş dielektrik rezonatörlerin etkisi olabilir.
60 GHz frekans bandında dielektrik fabry-perot yankılayıcılarının kullanılmasıyla mikroşerit yama antenlerin yönlülüklerinin arttırılması
Keywords: 60 GHz; Microstrip Patch Antennas; Patch Antennas; Inset-Fed; Insetfed Patch Antennas; Absorption; Oxygen Absorption; FDTD; Lorentz Model; Fabry Perot Theory; Fabry Perot Antenna; Dielectric Fabry Perot Antennas; Directivity; Directivity Enhancement; 60 GHz; Mikroşerit Yama Antenler; Yama Antenler; İlavebesleme; İçe Doğru Besleme; İlave-Beslemeli Yama Anten; Soğurma; Emilim; Oksijen Soğurması; FDTD; Lorentz Modeli; Fabry Perot Teoremi; Fabry Perot Anteni; Dielektrik Fabry Perot Antenleri; Yönlülük; Yönlülük Geliştirme